'The Lie of the Land: Representations of the South African Landscape.' By Michael Godby with essays by Cheryl Walker, Sandra Klopper and Brett Bennett - Penn, Nigel (Kronos: Southern African Histories, 2017)
This book was published to accompany the exhibition at the Iziko Michaelis Collection in the Old Town House in Cape Town between June and September 2010. As such it may be considered as a catalogue, but it is in fact a stand-alone publication, containing some of the best writing to date about theorising the South African landscape as well as a magnificent collection of visual representations of the landscape